(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Different parts of the skull bone have been used by researchers to determine sex. Owing to its anatomical position and compact structure the mastoid region of the skull resists physical damage and hence may remain intact in a fragmented skull. Most of the researchers have used dry skull bones or skull cephalograms for studying sexual dimorphism from mastoid triangle measurements. The present study is a retrospective CT scan-based study of the lateral aspect of the skull displaying the mastoid triangle in a defined South Indian population. The mastoid triangle is the area formed by straight lines joining the three points i.e., asterion, porion, and mastoidale. The asterion-porion length, asterion-mastoidale length, porion-mastoidale length, area, and perimeter of the mastoid triangle of both sides were studied. All the measured parameters on both sides were found to be significantly different between the two genders. Among the measured parameters, the area of the mastoid triangle of the left side was found to be most significant in determining gender.